ANALISIS KUALITAS AIR TANAH DI KECAMATAN TERNATE SELATAN, KOTA TERNATE PROVINSI MALUKU UTARA - Said Hi Abbas; Firman Firman; Syarifullah Bundang (Fakultas Teknik Universitas Khairun, 2022)
Research on the analysis of groundwater quality in South Ternate District, Ternate City, North Maluku Province needs to be carried out considering that the community's water sources in the area come from groundwater (dug and drilled wells), so knowledge of groundwater quality in the form of pH, TDS, EC, and temperature be important. The purpose of this study is to determine the quality of groundwater; as well as recommendations related to groundwater quality in the South Ternate District area. The stages of the research method were carried out by collecting primary data in the form of well coordinates and elevation, physical properties of groundwater, groundwater quality measurement results and secondary data collection. The water quality results in the South Ternate District for the 40 samples measured ranged from pH 5.2 to 6.6; TDS 4-2150 ppm; EC 8-4240 µS/cm and temperature ranges from 26.5-29.7oC. Based on Permenkes Number 32 of 2017 concerning environmental health quality standards and water health requirements for sanitary hygiene purposes, only 3 wells had a pH in the range of 6.5-8.5, namely samples F-02, TO-01, and TO-02. The physical quality of groundwater shows that the closer to the east the pH is, the closer to neutral, while the west is lower. There are many low water pH because sampling is done in the dry season.Keywords: groundwater, water quality, pH, TDS, South Ternate